Optimising The Potential of The Terasi Puger No. 1 through The Implementation of Digital Product Management and Marketing - Iwan Wicaksono; Globila Nurika; Mochammad Farid Afandi; Sallimah Mohd Salleh (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to optimize the potential of MSME Terasi Puger No. 1 in Puger Kulon Village, Jember, through improvements in production management and digital marketing strategies. The program employed a Participatory Rural Appraisal (PRA) approach involving the owner and workers in training, mentoring, and direct implementation. The interventions included the application of lean manufacturing (5S), the development and implementation of Standard Operating Procedures (SOPs) for occupational safety, hygiene, and sanitation, the provision of safety equipment, the introduction of vacuum-sealed packaging with a redesigned logo, and the utilization of e-commerce platforms and social media supported by simple accounting software. The results indicate measurable performance improvements, including the establishment of standardized production procedures, improved organization of raw material and product storage, consistent use of personal protective equipment, and safer workplace conditions. The adoption of airtight packaging enhanced product durability and reduced the risk of contamination during distribution. Marketing performance improved through the activation of online sales channels, diversified packaging sizes (100 g, 0.5 kg, and 1 kg), and expanded market access beyond previous distribution areas that were limited to intermediary-based sales in Jember, Banyuwangi, and Lumajang. In addition, systematic financial recording enabled better monitoring of operational costs and revenues. In conclusion, the integration of clean production management, packaging innovation, and digital marketing strengthened operational efficiency, broadened market reach, and improved business competitiveness, contributing to the long-term sustainability of the enterprise.